MEDIA USE AND HAPPINESS IN SERBIA - LJubiša Bojić; Maja Pavlović (Srpska Politička Misao)
The Annual Attitude Examination Survey consisting of 366 questions was deployed on nationally representative sample in Serbia to get 2608 responses on the Oxford Happiness Inventory and Multiple Lickert scale questions concerning attitudes, fears, media use and closeness of different social categories to the participants. Research results confirm all hypotheses. Quantity of television use is negatively correlated to happiness. As for the quality of newspapers use, those consuming contents such as culture, sports and IT are happier than others. When looking at television use, individuals that prefer programs such as cartoons, culture, music, fashion, science, IT and sports are happier than others. This is the first research examining relationship of happiness and quality of media use. Future research should encompass data from online social networks in order to see how positive and negative emotions of media users are related to media content they are exposed to.